An updated patent review: xanthine oxidase inhibitors for the treatment of hyperuricemia and gout (2011-2015). (4th March 2017) - Ojha, Ritu; Singh, Jagjeet; Ojha, Anu; Singh, Harbinder; Sharma, Sahil; Nepali, Kunal
ABSTRACT: Introduction: Xanthine oxidase (XO) is a versatile molybdoflavoprotein, widely distributed, occurring in milk, kidney, lung, heart, and vascular endothelium. Catalysis by XO to produce uric acid and reactive oxygen species leads to many diseases. Anti hyperuricemic therapy by xanthine oxidase inhibitors has been mainly employed for the treatment of gout. Area covered: This review covers the patent literature (2011–2015) and also presents the interesting strategies/rational approaches employed for the design of xanthine oxidase inhibitors reported recently. Expert opinion: Recent literature indicates that various non purine scaffolds have been extensively investigated for xanthine oxidase inhibition. The significant potential endowed by heteroaryl based compounds, in particularly fused heterocycles clearly highlights their clinical promise and the need for detailed investigation. Studies by various research groups have also revealed that the flavone framework is open for isosteric replacements and structural modifications for yielding potent non purine xanthine oxidase inhibitors. In addition, various plant extracts recently reported to possess significant xanthine oxidase inhibitory potential presents enough promise to initiate a screening program for the identification of other plant extracts and phytoconstituents possessing inhibitory potential towards the enzyme.